Activities of Musavat Party Between 1911-1922 - Budak, Alperen (Fırat University, 2018)
Besides nations who were under control of Russia, 1905 Russian Revolution affected Azerbaijan Turks as well and brought some important improvements in their life. Musavat Party one of the political bodies, founded by Turks who gained a restricted independent environment  thanks to Russian Revolution, became  the  most important and the most effective body in Azerbaijan political enviranment. Musavat Part carried out its activities secretly because it  was exposed to severe pressure and even its leader Mehmet Emin Resulzade had to manage the party’s activities out of Azerbaijan due to these pressures. However, he went on his duties and he became the most effective person in declaring Republic of Azerbaijan in 1918. Musavat Party which was founded officially in 1911 lost its power with Soviet invasion in 1920 and in 1922 it became uneffective complately.

1905 Rus Devrimi, Rusya hâkimiyetindeki diğer milletlerle birlikte Azerbaycan Türk’lerini de etkiledi ve siyasi hayatlarında önemli gelişmeler sağladı. Rus Devrimi’yle kısıtlı bir hürriyet ortamına kavuşan Türklerin kurmuş oldukları siyasi teşekküllerden biri olan Müsavat Partisi, Azerbaycan siyasi hayatında en etkili ve en önemli teşkilat olarak yerini almıştır. Müsavat Partisi, şiddetli baskılara maruz kaldığı için faaliyetlerini gizli yürütmüş ve hatta lideri Mehmet Emin Resulzade baskılar dolayısıyla parti çalışmalarını Azerbaycan dışından yönetmek zorunda kalmıştır. Fakat yine de faaliyetlerine devam etmiş ve 1918 yılında Azerbaycan Halk Cumhuriyeti’nin ilan edilmesinde en etkili unsur olarak kendisini göstermiştir. 1911 yılında resmen kurulan Müsavat Partisi, Azerbaycan’ın 1920’de Sovyet işgaline uğramasıyla güç kaybına uğramış ve 1922 yılında etkinliğini tamamen yitirmiştir.
MÜSAVAT PARTİSİNİN 1911 – 1922 YILLARI ARASINDAKİ FAALİYETLERİ